Influence of Principals’ Leadership Practices on Technology Integration in Public Secondary Schools in Mathare Sub-County, Nairobi, Kenya - Muinde John Makau; Kingi Mutinda Petronilla (East African Journal of Arts and Social Sciences, 2026)
Uneven integration of technology in Kenyan secondary schools is largely attributed to gaps in principals’ leadership practices. This study investigated the influence of principals’ leadership on technology integration in public secondary schools in Mathare Sub-County, Nairobi, Kenya, focusing on professional development provision and promotion of a collaborative culture. A descriptive survey design was adopted, targeting 12 principals and 48 teachers selected through census and stratified random sampling, respectively. Data were collected using questionnaires for teachers and semi-structured interviews for principals, with quantitative data analysed using descriptive statistics and qualitative data thematically analysed. Findings revealed that most principals actively support professional development through ICT training workshops, resource allocation, and peer-to-peer learning, enhancing teachers’ digital competencies. Additionally, principals foster a collaborative culture by involving teachers in ICT planning, promoting teamwork, and encouraging participatory decision-making, which positively influences technology integration. However, variations across schools were observed due to differences in resources and contextual challenges. The study concludes that principals’ leadership practices are critical enablers of effective ICT integration in school management and recommends strengthening professional development programs, enhancing collaborative structures, and allocating adequate resources to support technology adoption. The findings provide evidence-based insights for policy and practice on digital leadership in Kenyan secondary schools.